(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Nickel oxide (NiO) thin films were developed on soda lime glass using radio-frequencymagnetron sputtering at growth (substrate) temperatures ranging from room temperature (RT) to 400 °C.Modifications in structure, morphological, electrical, and optical properties were tracked as the substratetemperature varied. The XRD pattern shows that at 100 °C, the (2 0 0) preferred orientations predominatein the film. Nonetheless, EDX showed that NiO was decomposing all during the development of samplesat high temperatures, causing the (2 0 0) peak intensity to gradually decrease. The grains were evenlyspread, with a maximum grain size of 19.43 nm, as determined by FESEM examination of the surfacemorphology. In accordance with the XRD results, we find that raising the growth temperaturesignificantly reduces crystal quality and increases grain size. Maximum scanning probe microscopy(SPM) observed surface roughness (1.232 nm) occurs at room temperature. It was discovered thatincreasing the substrate temperature greatly decreased the electrical resistivity, from 2150 Ω cm to 72Ωcm. Transmission tests of light through NiO sheets show that the optical bandgap narrows from 3.8 to3.2 eV when the substrate is heated. The results raise the possibility that NiO films might be employed insolar energy systems.